A sala de apoio à aprendizagem na organização da escola em ciclos da rede pública municipal de Cuiabá-MT - Silva, Luci Oliveira Santana da (2012)
This research is part of the Master´s degree Course in Education PPGE/IE/UFMT, in the Research Line School Organization, Training and Pedagogical Practices, and is linked to the Research Group Curriculum, Training and School Practices – GPCFOPE. This investigation takes a part of the proposal given by the School Organized by Cycles in the Municipal Public Education System of Cuiabá-MT, aiming at studying one of its main issues, the Learning Support Room. One of the objectives of this room is to assist the students that have difficulty in the learning process during the school phases/cycles. The guiding issue is summarized in the following question: how do teachers working in some schools organized by cycles of the municipal school systems of Cuiabá (re)contextualize the curriculum in the learning support room? From this questioning, this research aims to understand how the teachers (re)contextualize the school curriculum in the learning support room of schools organized by cycles in the municipal school system of Cuiabá/MT. The construction of the theoretical approach occurs through Ball (2002, 2004), Bernstein (1990) and Lopes´s contributions (2008) on the (re)contextualization theme. As a reference the dialogue among the scholars about the organization by cycle in the Brazilian school education, Mainardes (2007), Fernandes (2006), Barreto and Mitrulis (1999, 2004), Krug (2001), Fetzner (2007), Freitas (2004), and about the continued teacher´s training, Imbernón (2006), Garcia (1999) and Giroux (1997), and about the theme of human development, Wallon (1995), Piaget (2010) and Vygostsky (2010) is used. The curricular issues are based on the theoreticians: Silva (2007), Moreira (1999), Sacristán (2000) and mainly Pacheco (1996). The methodology used is of an interpretative qualitative approach, opting for the cycle of policies proposed by Ball et al. (2002). The subjects of the research are 29 (twenty-nine) teachers, and 05 (five) teaching in the Learning Support Room, 15 (fifteen) others, that have students who attend this class. 06 (six) pedagogical coordinators and 03 (three) school directors are also included, that contribute with data to subsidy the contextualization of the research object. For the data collection, official documents from the Municipal Secretariat of Education of Cuiabá-MT and of 04 (four) schools, questionnaires and observation in the learning support room were used. The data analysis indicates that the curricular policies in the cycle conception comprise both in the texts of the official (re)contextualization field and in the pedagogical (re)contextualization field. The texts produced from 1998 to 2000 and the new texts produced from 2007 to 2011, in the municipal school system, are documents that are always in an unfinished process with multiple readings and (re)readings in a constant interpretation and reinterpretation. And also in the case of the schools being studied, do not escape from the rules of (re)contextualization of the official and non official field, that present in their documents the process of (re)contextualization, since they are fragment reconstituted in the practice context, mixtures among several trends about the cycle and conception of a curriculum.